Human capital resource and environmental management practices among hotels in Malaysia - Muhammad Jamil, Che Zuriana; Mohamed, Rapiah; Zainal Affrin, Zaimah (American Scientific Publishers, 2015)
This study aims to explore the influence of human capital resources (i.e., top management support and employee empowerment) on environmental management practices in the hotel sector in Malaysia.A cross-sectional survey was carried out on the sample of 4-star and above hotels across the Peninsular Malaysia. In Malaysia, the hotel sector is the key player in the tourism industry with a high tendency to negatively affect the environment in which it operates.The study’s finding shows that only employee empowerment is positively and significantly associated with environmental management practice. This implicates that to achieve the eco-tourism strategies, it is imperative to provide a richer set of insights into the effective human capital resources.